Investigation of Five Organic Dyes in Ethanol and Butanol for Two-Color Laser-Induced Fluorescence Ratio Thermometry - Mishra, Yogeshwar Nath; Yoganantham, Ajeth; Kögl, Matthias; Zigan, Lars (Optics, 2020)
In this article, we compare absorption and temperature-dependent fluorescence spectra of five organic dyes for 2c-LIF (two-color laser-induced fluorescence) thermometry in ethanol and butanol. The dyes fluorescein, eosin Y, rhodamine B, rhodamine 6G, and sulforhodamine 101 individually mixed in ethanol and butanol were studied at liquid temperatures of 25–65 °C. The self-absorption spectral bands are analyzed along with intensity ratios and the respective sensitivities for one-dye and two-dye 2c-LIF thermometry are deduced. For one-dye 2c-LIF, rhodamine B showed the highest sensitivity of 2.93%/°C and 2.89%/°C in ethanol and butanol, respectively. Sulforhodamine 101 and rhodamine 6G showed the least sensitivities of 0.51%/°C and 1.24%/°C in ethanol and butanol, respectively. For two-dye 2c-LIF, rhodamine B/sulforhodamine 101 exhibited the highest temperature sensitivities of 2.39%/°C and 2.54%/°C in ethanol and butanol, respectively. The dye pair eosin Y/sulforhodamine 101 showed the least sensitivities of 0.15%/°C and 0.27%/°C in ethanol and butanol, respectively.
CRIS-Team Scopus Importer:2024-12-16
Keywords: biofuels; laser-induced fluorescence; sensitivity; solvents; thermometry